Analisis Faktor Yang Mempengaruhi Pengelolaan Barang Milik Daerah (BMD) Pada Organisasi Perangkat Daerah (OPD) Di Lingkungan Pemerintah Kota Pekanbaru - Ricardo Ricardo; Fitriani Astika; Doni Jepisah (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2022)
This study is to analyze the factors that influence the management of regional property in the Pekanbaru City Government. This research uses the SPSS application with multiple linear regression analysis methods. The results of this research show that the quality of the regional apparatus has a significant effect on the management of regional property with a significance value of (0.000) < (0.05) and tcount (9.225) > t table (1.977). Compliance with regulations has a significant effect on the management of regional with a significance value of (0.028) < (0.05) and tcount (-2.218) > -ttable ((1.977). The use of information technology has no significant effect on the management of regional property with significance value (0.877) > (0.05) and tcount (-0.155) > -ttable (1.977).The government's internal control system has a significant effect on the management of regional property with a significance value of (0.008) <0.05 and tcount (2,679) > ttable (1,977).